PROCESS OF IMPLEMENTATION AND BENEFITS OF CRIME SCENE INVESTIGATION IN CASE OF CRIMINAL INVESTIGATION IN INDONESIA - Sri Endah Wahyuningsih; Teguh Prasetya; Muchamad Iksan (Jurnal Pembaharuan Hukum, 2018)
The case of crime scene conducted by the investigator is the main part in the disclosure of criminal case because in the crime scene can be found the interaction between the perpetrator of the crime, the evidence used and the witness/victim of crime at the time of the criminal event. Therefore this paper analyzes the implementation process and the benefits of crime scene in the process of criminal investigation in Indonesia. The research method used was sociological juridical, with primary and secondary data sources. Primary data were obtained by conducting interviews with respondents, they were investigators who investigate criminal case. The results of the research on the procedures for the implementation of the Crime Scene Investigation is started from the preparation of the crime scene, the trip to the scene, the first action at the crime scene (TPTKP). The crime scene investigation covers the general observations, photography, sketching, evidence collection, victim handling, and perpetrators of crime scene organization, and the end of the crime scene, which consists of consolidation, opening/exempting the crime scene, the making of investigation report at the scene, and the evacuation of activities. The benefit of crime scene investigation in criminal investigation is as evidence, source of information to look for witness, as source to look for evidence and as saber to find perpetrator, legal basis of investigator in execution of crime scene is JUKLAK (standard operational procedure) Police of Republic of Indonesia with number 04/1982 and JUKNIS Police of the Republic of Indonesia with the number JUKNIS 01/11/1982.